PENERAPAN DATA MINING UNTUK PREDIKSI PENJUALAN READYMIX MENGGUNAKAN METODE ALGORITMA C4.5 - hendra, hendra; Harman, Rika (LPPM Universitas Putera Batam, 2020)
PT remicon widyaprima is a manufacturing company which is engaged in readymix. Readymix is a mixing material consisting of sand, granite, cement and is also given a special additive that is admixture. PT remicon widyaprima in readymix production has various types of readymix (classes) that have different mutual supports, this is done by researchers who want to analyze. In conducting analisis the researchers used data mining techniques using the classification algorithm c4.5 which was performed using manual calculations and also the researchers used the weka application version 3.9.4 in order to find the results of the prediction of readymix sales at PT remicon widyaprima. from the results of this study, the data obtained can work accurately on the rules of each test, this can facilitate research based on data that has been obtained through the process of testing sales predictions categorized in several variables. Delivery of goods, product quality, product prices, product prices, guarantee / resistance concrete readymix, type readymix and capacity. The researcher used 2 decision variables namely buy readymix and not buy readymix.